Thermal Time Requirement for Fruit Development and Maturity of Jujube (Zizyphus mauritiana) Grown Under Rainfed Conditions in Indian Hot Desert - Singh, R S; Prasad, R N; Gupta, J P; Vashitha, B B; Ramakrishna, Y S (Annals of Arid Zone, 2016)
Relationships between phenological stages in three promising cultivars of jujube (viz., Tikadi, Seb and Gola) and ambient temperature were worked out for ;10 established orchard in arid sub-tropical climate of NW India under rain fed conditions. It was observed that Gala fruits mature early because they need relatively lesser thermal time (heat units), around 168919 degree Celsius days (°Cd) than others, after fruit selling. Tikadi and Gala cultivars required 335°Cd and 88°Cd for a mm increase in their fruit size, respectively. This could be one of the reasons for the faster development rate of Gola fruits. Thermal time calculated for the fruit maturity of different cultivars during three consecutive years 1990-93, were used for predicting the fruit maturity time during the next two seasons, 1993-94 and 1994-95. Heat use efficiency of Gala fruits was the highest (4.57 kg fruit ha -1 °Cd-1 followed by Tikadi and Seb cultivars.